Trade liberalization along the firm size distribution: The case of the EU-South Korea FTA - Sonali Chowdhry; Gabriel Felbermayr (Review of International Economics, 2023)
Leading theories suggest that amongst continuing exporters, lower variable trade costs should boost exports of smaller firms by the same or greater percentage rate than larger firms. However, investigating the impact of the deep EU-South Korea FTA with French customs data, we find robust evidence to the contrary. Applying a triple-difference framework, we report that the FTA increased sales in the top quartile of continuous exporters by 71.5% points more than in the bottom quartile. More than 90% of that growth premium is driven by reductions in NTBs. These findings suggest an additional channel driving the distributional effects of FTAs.
Keywords: 330; firm heterogeneity; nontariff barriers; trade policy